Neonatal Myasthenia Gravis - J Gordon Millichap (Pediatric Neurology Briefs)
The advantages of electrodiagnosis in a premature infant with neonatal myasthenia gravis are proposed by the Dept of Rehabilitation Medicine, Children’s Hospital and Medical Center, Univ of Washington School of Medicine, Seattle, WA.